Agro-Industrial Waste as a Source of Raw Material: Eggshell and Ash of Useful for the Synthesis of Hydroxyapatite - Elizondo Villarreal, Nora; Verástegui Domínguez, Luz Hypatia; Quijano Briones, José de Jesús; Vázquez Rodríguez, Francisco Javier; Rodríguez Castellanos, Edén Amaral; López Cuéllar, Enrique Manuel; Torres López, Ernesto; Castaño Meneses, Víctor Manuel (2022)
Agave salmiana ash and poultry eggshell powder as CaO sources were used for obtaining nanostructured hydroxyapatite (HAP). The synthesis was carried out by the Green Chemistry Hydrothermal Biosynthesis at 180°C with a pH of 5, by reacting CaO from Agave Salmiana ash and Eggshell powder, with dibasic calcium phosphate (CaHPO4•2H2O) in an aqueous solution, with Aloe barbadensis extract. The product was characterized by X-ray diffraction, Fourier-transform infrared spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), and Transmission Electron Microscopy (TEM). The size and shape of the hydroxyapatite particles changed dramatically in the presence of Aloe barbadensis. Large crystals of Hydroxyapatite were observed when Eggshell powder and Agave salmiana ash were used as raw materials in the presence of the Aloe barbadensis surfactant. Crystals with shapes of ribbons and plates from 1 micrometers to 8 micrometers were observed when using the eggshell powder in the presence of Aloe barbadensis and, in the case of Agave salmiana ash in the presence of Aloe barbadensis, crystals with shapes of quadrangular prisms and hexagonal (polyhedra) with sizes from 2 micrometers to 20 micrometers were observed. Hydroxyapatite was therefore successfully biosynthesized by a green and sustainable method that reduces the environmental impact.